A genetic polymorphism at miR‐526b binding‐site in the lincRNA‐NR_024015 exon confers risk of esophageal squamous cell carcinoma in a population of North China. Issue 3 (22nd September 2016) - Han, Lijie; Liu, Shengnan; Liang, Jia; Guo, Yanli; Shen, Supeng; Guo, Xin; Dong, Zhiming; Guo, Wei
Abstract : Esophageal squamous cell carcinoma (ESCC) may be caused by a combination of environmental factors and genetic variants. The present study was to evaluate the association between haplotype‐tagging SNPs (htSNPs) of lincRNA‐NR_024015 and the risk of ESCC. We selected htSNPs across the whole 1469 bp lincRNA‐NR_024015 locus and 2 kb upstream as well as 2 kb downstream regions of the gene and conducted a case‐control study in 581 ESCC cases and 677 healthy controls to test the effects of functional lincRNA‐NR_024015 htSNPs on ESCC susceptibility. Of the seven potential functional htSNPs, rs8506 AA genotype was found to be associated with increased risk of ESCC. Further stratification analysis showed that the risk effect was more pronounced in male patients and patients with TNM stage III and IV. LincRNA‐NR_024015 was predominantly expressed in cytoplasm of esophageal cancer cells. The expression level of lincRNA‐NR_024015 in ESCC tumor tissues was significantly higher than that in corresponding normal tissues and rs8506 genotype has a genotype‐specific effect on lincRNA‐NR_024015 expression. Furthermore, rs8506 G to A variant might influence lincRNA‐NR_024015 expression and function by disrupting the binding of hsa‐miR‐526b to the site. High expression level of lincRNA‐NR_024015 and rs8506 A allele were associated with poor ESCC patients' survival. These findings indicate that functional polymorphism rs8506 G>A in lincRNA‐NR_024015 exon may be a genetic modifier for the development of ESCC and lincRNA‐NR_024015 may be a useful marker for the prediction of the biological behavior of ESCC. © 2016 Wiley Periodicals, Inc.